The Influence of Isra ̂îliyya ̂t on the Interpretation of Women’s Issues in Jâmi’ al-Bayân fî Ta`wîl al-Āy al-Qur’ân by Muhammad ibn Jarir al-Tabari (224–310 AH) - Zahratunnisa Zahratunnisa; Muhammad Hariyadi; Iwan Satiri (ZAD Al-Mufassirin, 2026)
The massive presence of Isr îliyy t in Ath-Thabari’s exegesis is considered to have a negative impact in two ways: first, the tendency to accept it as truth because it appears in a trusted exegetical work; and second, the biased narratives regarding women often lead to discrimination and negative stigmatization. This article seeks to understand the role of Isr îliyy t within Ath-Thabari’s interpretive framework and to assess the influence of Isra’iliyyat and weak hadiths on the exegesis of verses concerning women’s issues. Using Foucauldian theory, this literature review demonstrates that, as an object of discourse, Ath-Thabari’s exegesis is subject to the power of al-‘Ilm. At the same time, it negotiates the gaps in differing opinions, thereby producing an independent interpretive product. The findings of this study indicate that for Ath-Thabari, the Isr îliyy t do not serve as the basis for interpretation but rather as a form of support. Consequently, their inclusion in this exegesis does not influence the interpretive outcome, including that pertaining to women’s issues. The massive presence of Isr îliyy t in Ath-Thabari’s exegesis is considered to have a negative impact in two ways: first, the tendency to accept it as truth because it appears in a trusted exegetical work; and second, the biased narratives regarding women often lead to discrimination and negative stigmatization. This article seeks to understand the role of Isr îliyy t within Ath-Thabari’s interpretive framework and to assess the influence of Isra’iliyyat and weak hadiths on the exegesis of verses concerning women’s issues. Using Foucauldian theory, this literature review demonstrates that, as an object of discourse, Ath-Thabari’s exegesis is subject to the power of al-‘Ilm. At the same time, it negotiates the gaps in differing opinions, thereby producing an independent interpretive product. The findings of this study indicate that for Ath-Thabari, the Isr îliyy t do not serve as the basis for interpretation but rather as a form of support. Consequently, their inclusion in this exegesis does not influence the interpretive outcome, including that pertaining to women’s issues.